Revisiting Higher-Order Thinking Skills in Arabic Language Education: From Technical Adoption to Pedagogical Transformation in Higher Education - Siti Maisaroh; Naqi’ah Naqi’ah; Sulaiman Hasan (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
The growing emphasis on Higher-Order Thinking Skills (HOTS) in higher education has encouraged curriculum reform across disciplines, including Arabic language education. However, existing studies predominantly conceptualise HOTS as a set of instructional techniques rather than as an overarching pedagogical orientation. This qualitative interpretive study examines whether HOTS functions as a holistic pedagogical paradigm or remains a fragmented instructional component in tertiary Arabic language teaching. Data were collected from course syllabi, instructional materials, and semi-structured interviews with one lecturer and five undergraduate students at a State Islamic University in East Java, Indonesia. The data were analysed using thematic analysis. The findings reveal a notable misalignment between curriculum design and classroom implementation. Although official course documents promote higher-order cognitive competencies, instructional practices and assessment methods continue to emphasise lower-order linguistic knowledge through predominantly closed-ended tasks. Consequently, HOTS is implemented primarily as a technical enhancement, such as increasing task complexity, rather than as an epistemological framework guiding teaching and learning. Nevertheless, the emergence of several meaning-oriented learning activities indicates an initial shift toward more interpretive and reflective pedagogical practices. This study contributes to Arabic language education literature by reconceptualising HOTS as an epistemological foundation that requires alignment among curriculum, pedagogy, and assessment. The findings also provide practical implications for curriculum developers and teacher educators seeking to strengthen HOTS implementation in tertiary Arabic language programmes.